Glass fiber-reinforced composite resin as fixed space maintainers in children: 12-month clinical follow-up - (:unkn) unknown (My University, 2005)
PURPOSE: The purpose of this clinical evaluation was to assess fixed space maintainers for child patients whose missing primary molars were replaced with space maintainers made with everStick during a 12-month follow-up period. EverStick is a semi-manufactured product made of glass fibers, thermoplastic polymer, and light-curing resin matrix for reinforcing the dental polymer. METHODS: Twenty-three clinical cases presented in this paper were evaluated in the Department of Pediatric Dentistry, Marmara University, Istanbul, Turkey. EverStick was used as part of a space maintainer on occasions where 1 or 2 teeth were lost in either the maxillary or mandibular arch. RESULTS: This study showed that the glass fiber-reinforced composite resin space maintainers functioned well during a mid-term evaluation. CONCLUSIONS: Clinical advantages of everStick include: (1) cost and time savings; (2) no need for a cast model; (3) no second visit; (4) easy to apply; (5) reliable adhesive bonding; (6) no metal allergy; (7) easy to clean; (8) natural feel; and (9) esthetically desirable.
Keywords: Female; Humans; Male; Follow-Up Studies; Child; Orthodontic Appliances; Composite Resins; Orthodontic Appliance Design; Glass; Space Maintenance, Orthodontic